Effects of Predicted Reduced Summer Rainfall on Growth and Development of Silver Birch (Betula Pendula Roth) and Downy Birch (Betula pubescens Ehrh) - Pradhan, Dhirendar Kumar; Cahalan, Christine; Ulak, Sunita (Forestry: Journal of Institute of Forestry, Nepal, 2018)
Climate is one of the major factors that govern the distribution of tree species. Climate change has already affected the growth, structure and distribution of trees and woodlands. Global climate change projections are wetter winters, drier summers and significance changes in temperature regimes in the next few decades. The main objective of this study was to experimentally demonstrate the effects of decline in summer rainfall, as predicted by UKCP09/IPCC, on height and diameter growth in two co-occurring silver birch (Betula pendula Roth) and downy birch (Betula pubescens Ehrh) and provide further understanding of the changes in growth and development in response to a decrease in water availability. One-year-old seedlings were grown in a temperature-controlled greenhouse for eight weeks in a split-plot experimental design. Their height and diameter were measured and analyzed. Result showed that plant height and diameter was significantly reduced with increased water stress. B. pendula showed higher physiological traits indicating that this species can perform better than B. pubescensin water-deficit conditions.